Atribut-Atribut Yang Menjadi Prioritas Untuk Peningkatan Kualitas Layanan Di Patra Semarang Convention Hotel - Aries Susanty; Arief Chandra Putra Buana (Jurnal Teknik Industri, 2011)
This paper is the result of a research that aimed to evaluate the quality of services at Patra Semarang Convention Hotel by using the Service Quality (SERVQUAL) and Importance Performance Matrix, and provide corrective suggestions for improving service quality on some priority attribute by using Quality Function Deployment (QFD) in order to clarify the follow-up should be done to close the gap that happened between acceptable and what is expected by the customer. In this paper, evaluation of service quality is assessed through five gaps (gap 1untill gap 5) that occurred. This evaluation is done by distributing questionnaires to customers (110 respondents) and to the employee (85 respondents). Then, the results of these evaluation are placed in the quadrants contained on Importance Performance Matrix (IPM) (mapped) in order to capture the attributes that really matter to the satisfaction of the customers but their performance is still very low (negative). Result of this mapping shows that the Patra Semarang Convention Hotel should focus its quality improvement services to the five important attributes, i.e: easiness to access the information from internet, clarity of delivery of new information by employee, cleanliness of the hotel, availability of adequate parking area, and speed of employees in responding to the consumer complaints. All this important attributes will be a priority in product planning for improvements the quality of services provided.